SCImago, Eigenfactor Score and H5 Index Journal Rank indicator : alternatives to the Journal Impact Factor for water resources journals - Ahmad, Shakil (2021)
Objective. This study investigated the possibility of SCImago Journal Rank (SJR), Eigenfactor Score (ES) and H5 Index indicators as alternatives to the Journal Impact Factor (JIF) in the field of water resources. Method. The SJR, ES, H5 index and JIF scores and ranking of water resources journals were downloaded from the relevant websites. Pearson and Spearman correlation coefficients were calculated to test hypotheses for association between the four journal quality metrics. Results. Strong positive correlations were found between the scores and rank order based on the SJR, ES, H5 and JIF of selected journals. Recommendation. Hence, academics and researchers in water resources can use the SJR, ES and H5 indicators as alternatives to JIF for evaluation and judgment of scientific journals in the area.